2016
DOI: 10.1007/s00439-016-1746-7
|View full text |Cite
|
Sign up to set email alerts
|

A common variant in CLDN14 causes precipitous, prelingual sensorineural hearing loss in multiple families due to founder effect

Abstract: Genetic isolates provide unprecedented opportunities to identify pathogenic mutations and explore the full natural history of clinically heterogeneous phenotypes such as hearing loss. We noticed a unique audioprofile, characterized by prelingual and rapid deterioration of hearing thresholds at frequencies >0.5 kHz in several adults from unrelated families from the island population of Newfoundland. Targeted serial Sanger sequencing of probands for deafness alleles (n = 23) that we previously identified in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Until Pater et al reported the progression of HL [29], the phenotype of DFNB29 was associated with non-progressive, congenital or prelingual HL with a variable degree of severity [13,26,27,28]. In this report, serial audiograms showed hearing deterioration especially at low frequencies (125 to 500 Hz).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Until Pater et al reported the progression of HL [29], the phenotype of DFNB29 was associated with non-progressive, congenital or prelingual HL with a variable degree of severity [13,26,27,28]. In this report, serial audiograms showed hearing deterioration especially at low frequencies (125 to 500 Hz).…”
Section: Discussionmentioning
confidence: 64%
“…In clear contrast to this, variants of CLDN14 account for 2.25% of autosomal recessive HL in the Pakistani population. In this study, the patient was identified from a non-consanguineous family and the parents of the proband were from a geographically remote area, whereas almost all of the previous reports were from consanguineous families [13,27,28,29]. As no pathogenic CLDN14 variants were found in our cohort, but one HL patient with a homozygous CLDN14 variant was identified, it is necessary to consider such rare HL cases.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…While most of the variants in CLDN14 that lead to hearing loss in different populations were missense variants ( Supplementary Table 3 ), nonsense variants were only found in this study and in one family from Pakistan (Lee et al, 2012). Variants of CLDN14 have been previously associated with hearing loss in Canada, Pakistan, India and Morocco (Wilcox et al, 2001; Bashir et al, 2010; Lee et al, 2012; Bashir et al, 2013; Charif et al, 2013; Pandey et al, 2017; Pater et al, 2017) ( Supplementary Table 3 ). In addition, some studies showed the absence of variants in the CLDN14 gene for other populations such as Tunisia, Turkey and China (Uyguner et al, 2003; Belguith et al, 2009; Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is the second documented evidence for a founder variant in the CLDN14 gene. The first founder effect has been reported for the c.488C>T variant that was predominant in the island population of Newfoundland (Pater et al, 2017).…”
Section: Discussionmentioning
confidence: 99%